Hermeneutical reasons of the critique of transcendental epistemology - Mikołajczyk, Hubert T. (Folia Philosophica, 2009)
In this paper I attempt to move the value of philosophical thinking from the formal framework of transcendentalism to its historical aspect. For this reason I see the watershed of philosophy in its transition from a monological to dialogical thinking. Hence, hermeneutics, which undertakes this task, has contributed to the renaissance of Socratic philosophy and has pinpointed the narrative point of view of the philosophical reflection as the history-justified moment of determination of truth. Hence, I shall argue that the verification of the transcendental consciousness by its confrontation with historical consciousness creates the real hermeneutical clou of the post-Kantian philosophical investigations.